Entendendo o comportamento canino: estudo das causas de agressão e sua influência na profilaxia da raiva humana - Nunes, Juliana Olivencia Ramalho [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
There are many benefits generated from the interaction between humans and animals. Mutual way, there are advantages to humans and animals, and between animals, particularly the dog. However, human company may adversely reflect on canine behavior resulting in aggression which, in turn, represent a serious problem for public health. In this sense, this research proposed to study the attacks of dogs to humans, involving the canine behavior. The study was conducted in the municipality of Descalvado, located in São Paulo, southeastern Brazil, by analyzing data from human attendance records occurred in 2014, obtained from the System for Notifiable Diseases Information (SINAN) as well as direct interviews with people bitten and with the owners of the biter dogs, through a questionnaire. Descriptive analysis was performed with frequencies of study and qualitative analysis with content analysis. In the 142 reports of assaults, the canine species predominated among aggressors (74.4%). Of assault people, 46.5% were adults between 20 and 59 years and owners of the dogs, with 42.2% of the interviewed people. The bite was the predominant type of injury (97.2%) in a unique way (66.4%), superficial (51.8%), mainly in hands and feet (43.6%). The procedure adopted more often for post-exposure prophylactic treatment was the observation of the animal associated with vaccination (68.3%). The biter dogs, 70.2% were male, 67.4% adults, 50% were vaccinated against rabies and 9.4% were sterilized. Among the biter dogs, 41.4% walked inappropriately (loose and unsupervised). 41.5% of the biter dogs acted amicably with those members of the household. A reserved attitude was the most frequent behavior demonstrated by the biter dogs for both people who know the dog (but not residing in the same household), and for people unaware of the dog in 39.1% of the interviews. With children, 34.8% of biter dogs showed like children. Based on the data, the reasons that ...

São muitos os benefícios gerados a partir da interação entre seres humanos e animais. De forma mútua, há vantagens para os seres humanos e animais, e, entre os animais, principalmente o cão. No entanto, a companhia humana pode refletir negativamente no comportamento canino resultando em agressões que, por sua vez, representam um sério problema para a saúde pública. Nesse sentido, a presente pesquisa propôs estudar as agressões de cães a humanos, envolvendo o comportamento canino. O estudo foi realizado no Município de Descalvado, localizado no Estado de São Paulo, região sudeste brasileira, por meio da análise de dados das fichas de atendimento para profilaxia da raiva humana ocorridos em 2014, obtidos a partir do Sistema de Informações de Agravos de Notificação (SINAN), além de entrevistas feitas diretas com pessoas agredidas e com as pessoas tidas como tutoras dos cães agressores, por meio de questionário. Foi realizada análise descritiva com estudo de frequências e análise qualitativa com a Análise de Conteúdo. Das 142 notificações de agressões, a espécie canina predominou entre os agressores (74,4%). Das pessoas agredidas, 46,5% eram adultos entre 20 a 59 anos e tutora dos cães, com 42,2% das pessoas entrevistadas. A mordedura predominou como tipo de lesão (97,2%) de forma única (66,4%), superficial (51,8%), principalmente em mãos e pés (43,6%). O procedimento adotado com maior frequência para o tratamento profilático pós-exposição foi a observação do animal associado à vacinação (68,3%). Dos cães agressores, 70,2% era macho, 67,4% adulto, 50% eram vacinados contra raiva e 9,4% eram esterilizados. Dentre os cães agressores, 41,4% passeavam de forma inadequada (solta e sem supervisão). 41,5% dos cães agressores agiam de forma amigável com as pessoas membros da casa. Uma atitude reservada foi o comportamento mais frequente demonstrado pelos cães agressores tanto para as pessoas que o...
Keywords: Cães; Cães - Comportamento; Mordeduras, picadas, etc; Hidrofobia; Hidrofobia - Prevenção; Rabies